The Inhibitory Activity of Curcumin on P-Glycoprotein and Its Uptake by and Efflux from LS180 Cells Is Not Affected by Its Galenic Formulation - Sandra Flory (MDPI AG, 2021)
The biological activities of curcumin in humans, including its antioxidative and anti-inflammatory functions, are limited by its naturally low bioavailability. Different formulation strategies have been developed, but the uptake of curcumin from these galenic formulations into and efflux from intestinal cells, which may be critical processes limiting bioavailability, have not been directly compared. Furthermore, little is known about their effect on P-glycoprotein activity, an important determinant of the pharmacokinetics of potentially co-administered drugs. P-glycoprotein activity was determined in LS180 cells, incubated with 30 or 60 µmol/L of curcumin in the form of seven different formulations or native curcuma extract for 1 h. All formulations inhibited P-glycoprotein activity at both concentrations. Curcumin uptake, after 1 h incubation of LS180 cells with the formulations (60 µmol/L), showed significant variability but no consistent effects. After 1 h pre-treatment with the formulations and further 8 h with curcumin-free medium, curcumin in cell culture supernatants, reflecting the efflux, differed between individual formulations, again without a clear effect. In conclusion, curcumin inhibits P-glycoprotein activity independently of its formulation. Its uptake by and efflux from intestinal cells was not significantly different between formulations, indicating that these processes are not important regulatory points for its bioavailability.